5-HT(1A), 5-HT(2A), and 5-HT(2C) receptor mRNA modulation by antidepressant treatment in the chronic mild stress model of depression: sex differences exposed. - Pitychoutis, P M; Dalla, C; Sideris, A C; Tsonis, P A; Papadopoulou-Daifoti, Z. (Neuroscience, 2012)
It is well established that women experience major depression at roughly twice the rate of men. Interestingly, accumulating clinical and experimental evidence shows that the responsiveness of males and females to antidepressant pharmacotherapy, and particularly to tricyclic antidepressants (TCAs), is sex-differentiated. Herein, we investigated whether exposure of male and female rats to the chronic mild stress (CMS) model of depression, as well as treatment with the TCA clomipramine may affect serotonergic receptors' (5-HTRs) mRNA expression in a sex-dependent manner. Male and female rats were subjected to CMS for 4 weeks and during the next 4 weeks they concurrently received clomipramine treatment (10 mg/ml/kg). CMS and clomipramine's effects on 5-HT(1A)R, 5-HT(2A)R, and 5-HT(2C)R mRNA expression were assessed by in situ hybridization histochemistry in selected subfields of the hippocampus and in the lateral orbitofrontal cortex (OFC), two regions implicated in the pathophysiology of major depression. CMS and clomipramine treatment induced sex-differentiated effects on rats' hedonic status and enhanced 5-HT(1A)R mRNA expression in the cornu ammonis 1 (CA1) hippocampal region of male rats. Additionally, CMS attenuated 5-HT(1A)R mRNA expression in the OFC of male rats and clomipramine reversed this effect. Moreover, 5-HT(2A)R mRNA levels in the OFC were enhanced in females but decreased in males, while clomipramine reversed this effect only in females. CMS increased 5-HT2CR mRNA expression in the CA4 region of both sexes and this effect was attenuated by clomipramine. Present data exposed that both CMS and clomipramine treatment may induce sex-differentiated and region-distinctive effects on 5-HTRs mRNA expression and further implicate the serotonergic system in the manifestation of sexually dimorphic neurobehavioral responses to stress.
Keywords: Animals; Antidepressive Agents, Tricyclic; Brain; Clomipramine; Depression; Disease Models, Animal; Female; In Situ Hybridization; Male; Rats; Rats, Sprague-Dawley; Receptors, Serotonin; RNA, Messenger; Sex Characteristics; Stress, Psychological